(untitled) (The Strategic Review for Southern Africa, 2020)
Major changes in the global governance architecture have markedly impacted upon and considerably changed the situation in Southern Africa since this journal was established 35 years ago. These shifts have also modified the approach documented in the periodical. With this issue, the Strategic Review enters another stage in its development. In pursuance of being a relevant source of information, profound analysis and engagement with topical policy matters, it is representing academically sound Southern African perspectives, as well as perspectives on Southern Africa. At the same time, it adds voices from civil society and other agencies, contributing in their way to necessary debates. The new blend offers further reflections and dimensions to provoke fruitful discourses not only confined to a purely academic analysis.